OPTIMIZATION OF PRICING AND COST PLANNING USING LINEAR FUNCTIONS: AN ECONOMIC MATHEMATICS PERSPECTIVE ON FINANCIAL STRATEGY AT CAKE MY DAY - Hery saputra; Nina Zakiah; Nurina Happy (Adisam Publisher, 2025)
Pricing and cost planning are critical aspects of business management, especially for small enterprises like the